Treatment efficacy on the cognitive competence of convicted intimate partner violence offenders - Arias, Esther; Arce , Ramón; Vázquez, María José; Marcos, Verónica (Anales de Psicología / Annals of Psychology, 2020)
The evaluation of the efficacy of treatment of batterers in Official or Couple Records is not valid, whilst the efficient interventions are focused on the empowerment of cognitive and behavioural competence. A field study for measuring the effects of the treatment on the cognitive competence was designed. A total of 100 batterers who had completed a community penitentiary intervention programme, were assessed pre- and post-treatment in cognitive competence i.e., self-concept, emotional intelligence, attribution of responsivity, cognitive skills to cope intimate-partner-related stressful events, expression and control of anger, and irrational beliefs and distorted thoughts. The results showed a significant effect of the treatment in the acquisition of cognitive competence skills. Succinctly, treatment empowered the general self-concept in 18.2%, and the internal dimensions of self-concept self-satisfaction in 33.5% and behaviour in 25.6%; and clarity to discriminate among moods in 31.8%. Moreover, treatment increased the assumption of internal responsivity in 31.8%; anger control in 19.1%; and the use of adaptive strategies to cope intimate-partner-related stressful events between 48.9% and 61.3%. Finally, treatment involved a fall in the use of maladaptive strategies to cope intimate-partner-related stressful events between 25.6% and 35.1%; and in the irrational beliefs and distorted thoughts related with the use of violence, in 78.2%, 48.2% y 63.6%, for use of violence, gender roles and emotional dependence, respectively. Nonetheless, not all the batterers benefited from treatment.